Clinical COPD Questionnaire score (CCQ) and mortality - Sundh, Josefin (Dove Medical Press, 2012)
INTRODUCTION: The Clinical COPD Questionnaire (CCQ) measures health status and can be used to assess health-related quality of life (HRQL). We investigated whether CCQ is also associated with mortality. METHODS: Some 1111 Swedish primary and secondary care chronic obstructive pulmonary disease (COPD) patients were randomly selected. Information from questionnaires and medical record review were obtained in 970 patients. The Swedish Board of Health and Welfare provided mortality data. Cox regression estimated survival, with adjustment for age, sex, heart disease, and lung function (for a subset with spirometry data, n = 530). Age and sex-standardized mortality ratios were calculated. RESULTS: Over 5 years, 220 patients (22.7%) died. Mortality risk was higher for mean CCQ ≥ 3 (37.8% died) compared with mean CCQ < 1 (11.4%), producing an adjusted hazard ratio (HR) (and 95% confidence interval [CI]) of 3.13 (1.98 to 4.95). After further adjustment for 1 second forced expiratory volume (expressed as percent of the European Community for Steel and Coal reference values ), the association remained (HR 2.94 [1.42 to 6.10]). The mortality risk was higher than in the general population, with standardized mortality ratio (and 95% CI) of 1.87 (1.18 to 2.80) with CCQ < 1, increasing to 6.05 (4.94 to 7.44) with CCQ ≥ 3. CONCLUSION: CCQ is predictive of mortality in COPD patients. As HRQL and mortality are both important clinical endpoints, CCQ could be used to target interventions.